Kajian Daerah Rawan Kebakaran Kota Langsa Menggunakan Metode Weight Product (WP) - heri irawan; Faiz Isma; Irwansyah (E-Jurnal Universitas Samudra, 2021)
This research was conducted to determine the Fire Prone Areas in Langsa City with the hope to realize the stability of regional development by minimizing potential losses that will be suffered and to attract investors to invest because there is a guarantee of security towards investment assets from fire hazards. By using the Weighting Product (WP) method to find out Fire-Prone Areas scattered in 5 Districts and 64 Gampongs in Langsa City based on predetermined criteria referring to Minister of Public Works Regulation No. 20 / PRT / M / 2009. From the results of the study using the Weighting Product (WP) method, it was found that there were 5 Gampong Subdistricts that were included in the prone category, 7 Gampong included in the rather vulnerable category and 1 in the relatively safe category. It can be said that this district must get serious attention considering the population density (KP), fire history, and the distance from the water supply is large enough so that the index value is very high. While the East Langsa sub-district was classified as a fairly safe sub-district from 15 villages, there were 8 villages that were in the safe category, 7 villages were classified as somewhat safe, and none of them were classified as somewhat vulnerable, vulnerable and very vulnerable. This is because the area of ​​east langsa is quite large with a population density that is not so dense and the range of water supply is close. Keywords: Fire-Prone Areas, WP